Impact of Home science training on Rural Women - Shashi Bhushan Kumar, Maya Kumari, Ashok Kumar, Pradeep Prasad (Indian Journal of Extension Education, 2022)
The human resource of country is highly significant and its development is essential for the progress and prosperity of the nation. Women constitute half of the population of the country. Their contribution to economy has become obvious that they are the pivot around whom the family, the society and whole humanity moves. However, their contribution is not well recognized and valued. Of course, in recent past a number of programmes and activities have. been undertaken to ameliorate this vulnerable section of population. But we have to yet go ’miles and miles together for the empowerment of women in real sense and spirit. In order to strengthen them and improve their status there is need to increase their participation in income generating activities. The status of women can improve through economic independence. The business and socio-cultural environment is now more conducive to encourage self employment among women. Realizing this fact lCAR launched Krishi Vigyan Kendras in the country which organise vocational training for rural youth and women on income generating activities such as tie and dye, bakery, preservation of fruits and vegetables, cutting and stitching of cloth, rakhi making and knitting of sweater etc. The training is an intellectual investment and effective method to bring desirable change in knowledge, skill and attitude of the trainees as these facilitate starting any particular income generating activities.